David Procedure for Aortic Root Aneurysm in a Post-Mitral Valve Repair patient with Marfan’s Syndrome – a Case Report. - Chanda, P K; Gupta, Saikat Das; Idhrees, A Mohammed; Rahman, Sheikh Nafis Ur; Hoque, Mozibul (Bangladesh Heart Journal, 2024)
Marfan’s syndrome is a multisystem connective tissue disorder caused by mutation of FBN1 gene, frequently affects the human cardiac valves. These patients commonly die due to cardiovascular diseases. David procedure has been recognized as a durable treatment option in younger adults for aortic root replacement in aortic aneurysm. But performing a David re-implantation for aortic root replacement in a post cardiac (mitral valve repair/MVR) surgery patient is not an easy task. We hereby present a case of successful David re-implantation of aortic root in a young post MVR patient. (Bangladesh Heart Journal 2024; 39(2): 168-171